2017
DOI: 10.1002/jmv.24776
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of treatment efficacy and ALT non‐normalization with sofosbuvir/ribavirin therapy for patients with hepatitis C virus genotype 2

Abstract: The tolerability and efficacy of sofosbuvir and ribavirin in patients infected with hepatitis C virus (HCV) genotype 2 were investigated under actual clinical conditions. A total of 208 patients with chronic HCV genotype 2 infection were treated with sofosbuvir 400 mg and ribavirin (weight-based dosing) for 12 weeks. Treatment discontinuation and sustained virological response 12 (SVR12) were evaluated. Moreover, factors associated with SVR12, hemoglobin decreasing to less than 10 g/dL during treatment, and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The clinical impact of DAA RASs in the HCV NS5B region on sofosbuvir/ribavirin treatment failure is still unclear (5)(6)(7)25). The two patients who experienced relapse had cirrhosis, which is also one of the risk factors for HCV RNA reappearance (6), and did not have any RASs in the HCV NS5B polymerase region, which had been previously reported (25).…”
Section: Discussionmentioning
confidence: 89%
“…The clinical impact of DAA RASs in the HCV NS5B region on sofosbuvir/ribavirin treatment failure is still unclear (5)(6)(7)25). The two patients who experienced relapse had cirrhosis, which is also one of the risk factors for HCV RNA reappearance (6), and did not have any RASs in the HCV NS5B polymerase region, which had been previously reported (25).…”
Section: Discussionmentioning
confidence: 89%
“…Recently, the serum Mac‐2‐binding protein glycosylation isomer (M2BPGi) has emerged as a novel non‐invasive marker for liver fibrosis, particularly in patients with chronic HCV infection 17,18 . In addition, M2BPGi can also be used to predict HCV treatment outcome, including regimens with PEG‐IFN‐ or DAA‐based therapies 19–21 . Despite these data, there are limited studies that directly examine the usefulness of serial M2BPGi in monitoring fibrosis regression following DAA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 In addition, M2BPGi can also be used to predict HCV treatment outcome, including regimens with PEG-IFN-or DAA-based therapies. [19][20][21] Despite these data, there are limited studies that directly examine the usefulness of serial M2BPGi in monitoring fibrosis regression following DAA treatment. Therefore, this study was aimed at investigating the clinical utility of serum M2BPGi kinetics during elbasvir/grazoprevir (EBR/GZR) therapy in HCV mono-infected and HIV/HCV co-infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…[ 57 ] Watanabe et al assessed the potential predictive factors associated with SVR-12: they found that independent predictive factors were gender, age, body mass index, baseline values for ALT, White blood cells, platelet counts, total bilirubin, albumin, prothrombin time, α-fetoprotein, HCV-RNA, type-4 collagen, hyaluronic acid, HbA1c, naïve treatment versus re-treatment, RBV adherence, and chronic hepatitis/cirrhosis. [ 59 ] The differences between these studies could be explained by the different sample sizes, virus genotypes, clinical situations of the patients, types of patients regarding previous experience to antivirals, and the addition of SOF.…”
Section: Discussionmentioning
confidence: 99%